Multinomial subjective logic based extended trust propagation model - Jun-feng TIAN; Li-juan WU (Tongxin xuebao)
In order to improve the accurateness of trust evaluation and the applicability of subjective logic,a multinomial subjective logic based extended trust propagation model (MSL-ETPM) was presented,which was composed of trust fu-sion and trust transitivity.Making the fused opinion more accurate and more in line with the intuitive judgment of human,reputation-based fusion operator of multinomial opinions takes effects of the reputation value and observation circum-stance into consideration.Trust transitivity interprets multinomial opinion transitivity as meaning that transitivity process is binomial logical opinion and transitivity information is multinomial opinion,giving trust transitivity formula of multi-nomial opinion and proving related theorem.Finally,the accuracy and adaptability of the model are put to the proof by example analysis.